Effect of Acidity and Boiling Time on Food Contamination by Glass , Aluminium , Stainless Steel and Tefal Utensils in Iraqi Kitchens - Jassem M. A. Al – Hassien (Journal of Madenat Alelem University College, 2011)
In this research we studied the effect of acidity and heating time on food contamination using many types of utensils ( glass , light aluminium , heavy aluminium , stainless steel and tefal utensils ) found in Iraqi kitchens . The concentrations of Al , Fe and Pb were measured in foods , under investigation , after boiled for 45min and more than 90 min and acidified it by using Flame Atomic Absorpition Spectroscopy. Results showed that the glass utensils do not contaminate foods , wherease, the aluminium utensils showed an increase in Al levels in foods above its premicible limits . However Fe concentrasions remaind in normal acceptable levels by using glass or light aluminium utensils , whereas , it showed observed increase in its level by using heavy aluminium or tefal utensils . Al showed high stability in its level by using stainless steel or tefal utensils , whereas , Fe showed high excess in its level by using stainless steel utensils .